Structure and function of a novel lineage-specific neutralizing epitope on H protein of canine distemper virus - Bi, Zhenwei; Wang, Wenjie; Xia, Xingxia (Frontiers in Microbiology, 2023)
Canine distemper virus (CDV) infects many sensitive species worldwide and its host range is expanding. The hemagglutinin (H) protein, the major neutralizing target, binds to cellular receptors and subsequently triggers fusion for initial viral infection. So it’s necessary to clarify the precise neutralizing epitopes of H protein and extend the knowledge of mechanisms of virus neutralization. In this study, a neutralizing monoclonal antibody (mAb) 2D12 against CDV H protein, which had different reactivity with different CDV strains, was generated and characterized. A series of truncated H proteins were screened to define the minimal linear epitope 238DIEREFD244 recognized by 2D12. Further investigation revealed that the epitope was highly conserved in America-1 vaccine lineage of CDV strains, but different substitutions in the epitope appeared in CDV strains of the other lineages and two substitutions (D238Y and R241G) caused the change of antigenicity. Thus, the epitope represents a novel lineage-specific neutralizing target on H protein of CDV for differentiation of America-1 vaccine lineage and the other lineages of CDV strains. The epitope was identified to localize at the surface of H protein in two different positions in a three-dimensional (3D) structure, but not at the position of the receptor-binding site (RBS), so the mAb 2D12 that recognized the epitope did not inhibit binding of H protein to the receptor. But mAb 2D12 interfered with the H-F interaction for inhibiting membrane fusion, suggesting that the mAb plays key roles for formation of H-F protein oligomeric structure. Our data will contribute to the understanding of the structure, function, and antigenicity of CDV H protein and mechanisms of virus neutralization.